ANALYSIS OF THE INTERNAL AUDIT SUBDIVISION ACTIVITY IN THE CORPORATE SECTOR OF THE REPUBLIC OF MOLDOVA - PETREANU, Elena (Economy and Sociology, 2021)
The actuality of the topic results from the importance of internal audit for owners, potential investors and creditors, as well as from the significance of internal audit as a basic element in corporate governance. At the present moment, there are no studies on the current situation and the role of internal audit in the country’s corporate sector. Therefore, the author intended to perform the analysis of the internal audit subdivisions activity in the nominated sector. For this, the relevant research directions have been established, the purpose of which is to study the qualitative characteristics of the internal audit subdivisions. The author has conducted a qualitative study, through a semi-structured interview, and the information analyzed represents the October-December 2019 period. The main results of the study show that the basic functional tasks of an internal audit are the classic tasks, such as safety assessment and the effectiveness of internal control; monitoring the process of liquidating the weaknesses of the internal control system; developing recommendations for improving the internal control system. Failure to comply with the provisions of ISPPIA has been observed. The factors that most influence the activity of the internal audit subdivisions are their insufficient provision with employees and the duration of obtaining the necessary information. It was discovered that independent external evaluations are not performed and planned in the analyzed economic entities, which proves the non-compliance with ISPPIA, due to the lack of need for such an evaluation and the relatively short period of activity of internal audit subdivisions.